2019
DOI: 10.1055/a-1046-1404
|View full text |Cite|
|
Sign up to set email alerts
|

Protection of Curcumin against Streptozocin-Induced Pancreatic Cell Destruction in T2D Rats

Abstract: As a kind of traditional Chinese medicine extract, curcumin has been proven to be effective in inhibiting inflammation and apoptosis in pancreatic islet β cells in the streptozotocin-induced diabetes mellitus rat model, although the underlying mechanism has not yet been clarified. To examine the effect of curcumin on inflammation and apoptosis in pancreatic islet β cells, we established a type 2 diabetes rat model by feeding the animals a high-fat diet and intraperitoneally injecting streptozotocin. The curcum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Prior studies in this area have shown that TUNEL immunoreactivity in the pancreatic tissue is increased in rat models of type 2 diabetes, which is similar to our findings. 51,52 A decrease in cellular proliferation in the diabetic testicular tissues has been reported in previous studies. 53,54 In addition to type 1 diabetes models, PCNA immunoreactivity has been evaluated in type 2 diabetes models; Ranjan et al 55 reported that the PCNA immunoreactivity in testicular tissue decreased in diabetes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Prior studies in this area have shown that TUNEL immunoreactivity in the pancreatic tissue is increased in rat models of type 2 diabetes, which is similar to our findings. 51,52 A decrease in cellular proliferation in the diabetic testicular tissues has been reported in previous studies. 53,54 In addition to type 1 diabetes models, PCNA immunoreactivity has been evaluated in type 2 diabetes models; Ranjan et al 55 reported that the PCNA immunoreactivity in testicular tissue decreased in diabetes.…”
Section: Discussionsupporting
confidence: 70%
“…Prior studies in this area have shown that TUNEL immunoreactivity in the pancreatic tissue is increased in rat models of type 2 diabetes, which is similar to our findings. 51,52…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this issue led us to point out the antiapoptotic and the antifibrotic effects of curcumin here. The antiapoptotic effects of curcumin were found in different organ injuries including diabetes, nephrotoxicity, intestinal inflammation, neurotoxicity with several mechanisms (Loganes et al., 2017; Qihui, Shuntian, Xin, Xiaoxia, & Zhongpei, 2020; Soetikno et al., 2019; Sun et al., 2014). Both antiapoptotic and antifibrotic effects of curcumin were shown on the ALI model in mice.…”
Section: Therapeutic Effects Of Curcumin Against Covid‐19mentioning
confidence: 99%
“…28 Qihui et al showed that CUR inhibited inflammation and apoptosis in pancreatic islet β cells of diabetic rats. 29 Moreover, there are scientific reports that CUR may be neglected even in high concentrations in human and animals regarding its toxicity. [30][31][32] Our results match up with the study results that CUR is a great antioxidant.…”
Section: Discussionmentioning
confidence: 99%